Improved soil hydrological modeling with the implementation of salt-induced freezing point depression in CoupModel: Model calibration and validation - Wu, Mousong; Zhao, Qiang; Jansson, Per-Erik; Wu, Jingwei; Tan, Xiao; Duan, Zheng; Wang, Kang; Chen, Peng; Zheng, Minjie; Huang, Jiesheng; Zhang, Wenxin (Journal of hydrology (Amsterdam), 2021)
•Salts in frozen soils impact freezing point and vary with time during freezing.•Couplings in water, heat and energy processes were found in frozen soils simulation.•Boundary conditions were found to impact surface water and energy balance.•Salts transport was underestimated by the model. Soil freezing/thawing is an important mechanism to control soil water and heat redistribution in mid-to-high latitudes. Salt in the agricultural soil from mid-to-high latitudes can alter characteristics of soil freezing/thawing cycle and then affect soil thermal and hydrological processes in winter and finally cause salinization in spring. To quantify the impacts of soil salinization on soil water and heat transport in saline soils, we conducted field experiments on soil water and heat dynamics in two typical agricultural regions of northern China with different climate and soil conditions. The coupled soil heat and water model—CoupModel has been extended to account for the dynamic impacts of salt on freezing point depression. The newly-added module improved the representation of soil freezing point depression by significantly improving model performance between simulated and measured soil temperatures, especially around freezing point, with mean error (ME) for the soil temperature at various depths reduced by 16% to 77% for the entire winter period. With a systematic model calibration approach, processes related to energy balance and soil freezing/thawing have been well constrained for both study sites with different characteristics for soil hydrology and energy balance. The model generally showed good performance with respect to soil moisture and temperature for both the calibration and validation periods. Our study has demonstrated a new modeling approach to successfully account for the impacts of salt on soil freezing/thawing and the new module can be a useful tool to address the salinization problems in mid-to-high latitudes with respect to climate change and water management.